AB1173 Correlation between trabecular bone score (TBS) and naifold videocapillaroscopy in systemic sclerosispatients. (12th June 2018) - Casabella, A.; Ruaro, B.; Paolino, S.; Pizzorni, C.; Alessandri, E.; Seriolo, C.; Fasciolo, D.; Botticella, G.; Molfetta, L.; Odetti, P.; Seriolo, B.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is associated with an increased risk of altered bone and fractures as a result of multiple factors, including treatment-related side effects, low vitamin D serum concentrations and reduced physical activity. 1 Trabecular Bone Score (TBS) is an index extracted from dual-energy X-ray absorptiometry (DXA) analysis, that provides an indirect measurement of axial bone microarchitecture and bone quality(. 2 Objectives: The aim of this study was to evaluate possible correlation between bone quality, by TBS, and different levels of microvascular damage, as evaluated by nailfold videocapillaroscopy (NVC) patterns 3 in SSc patients and to compare the results regarding bone quality with RA patients and healthy subjects (CNT). Methods: Eighty-eight SSc patients, 98 rheumatoid arthritis (RA) patients and 60 CNT were studied. Bone Mineral Density (BMD, g/cm 2 ) of the lumbar spine (L1-L4) was analysed by dual-energy X-ray absorptiometry (DXA) scan. Lumbar spine bone quality was derived from each spine DXA examination using the TBS analysis. NVC patterns were analysed as previous reported. 3 All patients were subjected to 25 hydroxyvitamin D (25(OH)D ng/ml) serum dosage. Results: TBS values were found statistically higher in SSc with a "Early" NVC pattern, compared to the "Active" or "Late" pattern (1.182±0.1, 1.101±0.8, 1.074±0.1 respectively, p<0.001). No statistical significant difference was observed in the three groups about DXA values (p=0.13, for all areas).A total of 56/84 SSc patients (66%) as well as in 78/98 RA patients (80%) showed bone loss at DXA and BMD was found significantly lower than in the CNT (p<0.001). Similarly, lumbar spine TBS was found significantly lower in SSc and RA patients than in CNT (p<0.001). There was no statistically significant difference in the mean lumbar spine TBS between SSc and RA patients (p=0.238). Serum levels of 25 (OH) D were statistically significantly higher in patients with "Early" SSc pattern than in those both "Active" and "Late" pattern (19.1±7.5, 15.1±5.3, 12.1±7.1 respectively, p=0.002). Conclusions: The bone quality seems lower in SSc patients with more altered microvasculature ("Late" NVC pattern). The data obtained showed also a significantly lower bone quality (lower TBS and BMD) in SSc and RA patients compared to CNT. The association between bone damage and the "Late" advanced NVC pattern of microvascular damage, may suggest that tissue hypoxia/ischemia related to the diffuse microangiopathy might be a further promoting factor for osteoclastogenesis and bone loss. Our results support the development of a combined approach using both TBS and BMD for the assessment of bone microarchitecture/quality in SSc patients during their disease progression. References: [1] Cutolo M, et al. Autoimmun Rev2011;12:84–7. [2] Roux JP, et al. Osteoporosis Int2013; 24:2455–60. [3] Cutolo M, et al. J Rheumatol. 2000;27:155–60. Disclosure of Interest: None declared